Pelanggaran Prinsip Persona Grata Atas Penyerangan Duta Besar Ditinjau Dari Perspektif Hukum Internasional (Studi Kasus Penyerangan Duta Besar Amerika Serikat Di Benghazi Libya) - Desi Yunitasari (Jurnal Locus Delicti, 2020)
The development of human history has proven that relations between countries are inevitable and are a necessity and often cause conflicts. Along with its development, an unavoidable event is an increase in violations of the provisions of international law, especially with regard to the principle of persona grata where officials or diplomat representatives should get protection when it has been received and placed in the recipient country. As happened in mid-2012 namely regarding the bombing incident carried out through a rocket attack on the United States Embassy (Libya) Office, Libya, in Benghazi City, on September 11, 2012. The attack resulted in the Ambassador and three embassy staff killed. In research that uses normative juridical methods, it is necessary to use secondary data, such as books, laws, and research results on research topics to determine the extent of the legal consequences of the principle of persona grata that has been violated. Based on the results of the study explained that the Libyan Government is responsible for the incident because it fulfills two elements of state responsibility including act or omission that can be imputable to a country, and the act or omission constitutes a violation of an international obligation, especially regarding the principle of persona grata. The Government of Libya as the recipient country is obliged to be responsible based on the 1961 Vienna Convention Article 22 Paragraph (2). As the injured party, the United States can hold the Libyan government diplomatically responsible, namely negotiations, bearing in mind that the benefits of negotiation settlement can be measured in all aspects.